Sociocultural predictors of obligatory exercise in young men: A Polish-Chinese comparison - Guo, Shuai; Izydorczyk, Bernadetta; Lipowska, Małgorzata; Lizinczyk, Sebastian; Kamionka, Agata; Sajewicz-Radtke, Urszula; Radtke, Bartosz M.; Liu, Taofeng; Lipowski, Mariusz (Frontiers in Psychiatry, 2023)
Background Obligatory exercise has been shown to have negative physical and mental effects on exercisers and is more prevalent among young people. However, there is limited research on obligatory exercise among young men. Social comparison theory offers a novel perspective to explore the relationship between sociocultural factors and obligatory exercise among young men, which offers an opportunity to understand potential factors contributing to obligatory exercise among young men across different cultures. Method We recruited a purposive sample of young people aged 18-30 from Poland (n=79) and China (n=194). Participants completed self-report measures including the Sociocultural Attitudes Toward Appearance Questionnaire3, Inventory of Physical Activity Objectives, and Obligatory Exercise Questionnaire. In the data analysis stage, we examined the strength of the relationships between the independent variables and the dependent variable through multiple regression analysis, and tested the role of the mediating variables. Results The main analyses revealed that Internalization-Athlete was a common direct predictor of obligatory exercise for both Polish and Chinese young men; that there were direct sociocultural predictors of obligatory exercise that were only used in relation to Polish or Chinese young men; and that social adaptation goals for motivation for physical activity mediated the development of obligatory exercise for Polish and Chinese young men, and that there were cross-cultural differences. Conclusion Attention should be paid to their attitudes towards the idea of a muscular and athletic body and socially adapted physical activity motivations when understanding young men’s obligatory exercise, while also considering cross-cultural differences.